2009
DOI: 10.1093/sleep/32.8.1100
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Differences Predict Cognitive Vulnerability to Sleep Deprivation

Abstract: Differences in distributed WM pathways reflect, and may contribute to, a person's ability to function effectively when sleep deprived. The widespread nature of this effect supports previous views that TSD has a global effect on brain functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 9 publications
2
34
0
Order By: Relevance
“…Previous studies suggested that specific structural measures taken at rest may reflect the degree of individual cognitive vulnerability to sleep deprivation (Cui et al, 2015; Rocklage et al, 2009). Here, we found that structural changes occurring during extended wake can be used to predict individual vigilance levels, and may partially contribute to predict variation in specific behavioral measures related to performance in an impulse control test.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that specific structural measures taken at rest may reflect the degree of individual cognitive vulnerability to sleep deprivation (Cui et al, 2015; Rocklage et al, 2009). Here, we found that structural changes occurring during extended wake can be used to predict individual vigilance levels, and may partially contribute to predict variation in specific behavioral measures related to performance in an impulse control test.…”
Section: Discussionmentioning
confidence: 99%
“…These declines have been proposed to reflect lower thalamo-cortical functional connectivity (Babiloni et al, 2010). Previous research has shown that increased structural brain connectivity moderates the effects of sleep loss on cognition (Rocklage, Williams, Pacheco, & Schnyer, 2009). The present results suggest that changes in daily sleep patterns may also effect functional brain connectivity in ways that are currently not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…While the distribution of reaction times did not deviate from normality, the number of lapses per session followed a Poisson distribution and was accordingly modeled in the linear mixed-effects model. Based on the observation that vulnerability to sleep deprivation varies greatly across people (Van Dongen et al, 2004, 2012; Rocklage et al, 2009), we hypothesized that sleep-deprived participants with the most marked lack of increase in effective connectivity to eye-opening would be the ones to perform worst on the brief-stimulus reaction time task. For each subject, averages over the five post-sleep deprivation sessions were calculated both for the performance measures (reaction times and lapses) and for the relative change (ratio) of GC in the forward direction during the eyes-closed relative to eyes-closed periods.…”
Section: Methodsmentioning
confidence: 99%
“…Vigilance has been proposed as the cognitive process most sensitive to sleep deprivation in adults (Lim and Dinges, 2010) and the culprit of the performance degradation on other tasks (Philibert, 2005; Lim and Dinges, 2008, 2010). Of note, there are considerable trait-like individual differences in the effect of sleep deprivation on vigilance (Van Dongen et al, 2004, 2012; Rocklage et al, 2009). Pursuing the brain mechanisms involved in these individual differences in vulnerability is thus of considerable importance.…”
Section: Introductionmentioning
confidence: 99%